2017
DOI: 10.1097/mbc.0000000000000549
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the quality of care for haemophilia at the Yaoundé reference treatment Centre of Cameroon

Abstract: With a recently established Haemophilia Treatment Centre (HTC) in Yaoundé, Cameroon, over a hundred people living with haemophilia have been recruited and followed up at this centre. This study aimed at assessing the quality of haemophilia care provided at the HTC, in order to monitor and improve patient care. In February 2014, the HTC was assessed using recommended markers. Although few, the logistics and reagents for the diagnosis and treatment of haemophilia were available. There were seven trained workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…As a rare, chronic and cost‐intensive condition, haemophilia is obviously not a priority in developing countries where governments focus their limited resources on public health issues, such as nutrition, immunization, sanitation and treatment of infectious diseases . In sub‐Saharan African countries, research on haemophilia is limited, with data mainly coming from South Africa, Senegal, Zimbabwe, Nigeria and Cameroon . Epidemiological data on haemophilia in the Ivory Coast are scarce .…”
Section: Introductionmentioning
confidence: 99%
“…As a rare, chronic and cost‐intensive condition, haemophilia is obviously not a priority in developing countries where governments focus their limited resources on public health issues, such as nutrition, immunization, sanitation and treatment of infectious diseases . In sub‐Saharan African countries, research on haemophilia is limited, with data mainly coming from South Africa, Senegal, Zimbabwe, Nigeria and Cameroon . Epidemiological data on haemophilia in the Ivory Coast are scarce .…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, their analysis of the Quality of Life (QoL) in PLWH in the HTC in Yaoundé, and despite not meeting the ideal international standards, Nzometia et al reported significant improvement in the QoL of those using the facility. 15 Nevertheless, a few HTCs including that of Senegal in Dakar have both improved diagnosis, care and capacity building of care personnel. 16 This HTC has evolved to become a training center on hemophilia care, and hosting several workshops and seminars.…”
Section: Challengesmentioning
confidence: 99%
“…In Senegal, for example, a study reports a prevalence of 2.3/100 000 male births, accounting for only 11.6% of the expected figure in the country 2 . Very few studies have focused on haemophilia in sub‐Saharan Africa, the epidemiological data being mainly obtained from Senegal, 2 South Africa, 3 Zimbabwe, 4 Nigeria, 5 Cameroon 6 and Ivory Coast 7,8 . These studies highlight worrying trends as reported by Diop et al 2 who emphasize that most of the patients die very early in their childhood, during untreated haemorrhagic episodes due to the inaccessibility of factor concentrates replacement.…”
Section: Introductionmentioning
confidence: 99%